Acute vascular events as a possibly related adverse event of immunotherapy: a single-institute retrospective study. (October 2019) - Bar, Jair; Markel, Gal; Gottfried, Teodor; Percik, Ruth; Leibowitz-Amit, Raya; Berger, Raanan; Golan, Talia; Daher, Sameh; Taliansky, Alisa; Dudnik, Elizabeth; Shulman, Katerina; Urban, Damien; et al.
Abstract: Aim: Immune-related toxicities of immune checkpoint inhibitors (CPIs) require prompt diagnosis and treatment. Atherosclerosis has an inflammatory component; we speculated this inflammation could be enhanced by CPIs. We aimed to evaluate the risk of acute vascular events (AVEs) on CPIs. Methods: Patients treated by CPIs in Sheba Medical Center (Israel) between January 2015 and May 2018 were retrospectively identified from electronic medical records. AVEs were identified and verified by chart review. Age, sex, diabetes, hypertension, smoking, dyslipidemia, previous AVE, renal failure, cancer type and specific treatments were evaluated as potential risk factors. AVE rate on CPIs was compared with that on chemotherapy or on combined chemo-immunotherapy in patients with lung adenocarcinoma. Survival of patients with AVEs was compared with that of patients without AVEs. Results: CPI was administered to 1215 patients. AVEs within six months after CPI initiation occurred in 2.6% (95% confidence interval [CI]: 1.8–3.6) of patients, more common than in later time periods. In lung adenocarcinoma, event rate was 5.2% (95% CI: 2.8–9.2). Lung adenocarcinoma, prior AVE, hypertension and dyslipidemia were correlated with AVEs. AVE rate in patients with non-small cell lung cancer adenocarcinoma was similar whether on chemotherapy or on CPI. Survival of patients with AVEs was worse than that of those without AVEs. Conclusion: The similarly increased rates of AVEs for patients on CPI, on chemotherapy or on both suggest that although CPI may not augment the risk of AVE over that of chemotherapy, it carries a similar and significant risk of such adverse event. Caution should be exercised for patients with risk factors for AVEs. Highlights: Event rate on checkpoint inhibitors (CPIs) (2.6%) was in the same range as for patients on chemotherapy. CPIs were more common during 1–6 months from initiation vs. during 7–12 months. Of all patients with lung adenocarcinoma, 5.2% had an acute vascular event (AVE) within 6 months of starting CPIs. Past AVE, hypertension, dyslipidemia and lung adenocarcinoma were correlated with AVEs. AVE development on CPI conveys a significantly worth outcome.